2018
DOI: 10.3390/atmos9100373
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Source Apportionment of Summertime Volatile Organic Compounds in a Fast Developing City in the Yangtze River Delta, China

Abstract: Volatile organic compounds (VOCs) are crucial for ozone formation in the Yangtze River Delta (YRD) in China. The characteristics of ambient VOCs in Nantong, a fast developing city in the YRD, were studied. Sixty ambient air samples were taken at five sites in three sampling days during summer time. One hundred and five VOCs were measured, showing that VOC concentration varied between 27.5 ppbv to 33.1 ppbv at five sites; these levels were generally lower than those for some big Chinese cities like Beijing, Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…图式 9 芳香烃氧化过程 RO 的开环反应. 机制(a)参考 MCM (http://mcm.leeds.ac.uk/MCM-devel/roots.htt), 机制(b)参考 Wu 等 [62] 的研究, 机制(c) 参考 Wang 等 [28] 和 Xu 等 [27] 的研究 Scheme 9 RO ring open reactions during aromatic hydrocarbon oxidation mechanism. Mechanism (a) was refer to MCM (http://mcm.leeds.ac.uk/MCM-devel/roots.htt).…”
Section: H 转移反应mentioning
confidence: 99%
“…图式 9 芳香烃氧化过程 RO 的开环反应. 机制(a)参考 MCM (http://mcm.leeds.ac.uk/MCM-devel/roots.htt), 机制(b)参考 Wu 等 [62] 的研究, 机制(c) 参考 Wang 等 [28] 和 Xu 等 [27] 的研究 Scheme 9 RO ring open reactions during aromatic hydrocarbon oxidation mechanism. Mechanism (a) was refer to MCM (http://mcm.leeds.ac.uk/MCM-devel/roots.htt).…”
Section: H 转移反应mentioning
confidence: 99%
“…High B/T ratios reflect a longer transport of vehicular emissions from surrounding cities or result from older air masses due to their differences in lifetime [40]. B/T ratio > 1 reflects a source dominated by coal and biofuel burning, whereas B/T < 0.6 reflects vehicle emission dominated source [41]. The B/T ratio range in weekday (weekend) of 0.03±0.01 (0.04±0.01) at monitoring site was low and indicates that toluene was emitted near the source and associated mainly with vehicular emission.…”
Section: ) Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…78 In a heavy oil extraction area in Alberta, Canada, Aklilu et al, (2018), used PMF to apportion three tracer species: acetone (19%), benzene/hexane (7%), toluene/xylene (5%), and two factors: regional air mass (30%), oil evaporation (15%), for the elevated concentrations of 22 hydrocarbon VOCs. 79 In China, studies to apportion VOC sources in areas including oil fields and industrial parks, showed source categories associated with technical uses (i.e., oil refining processes, asphalt and foundry production) [80][81] while in urban areas, such as Taiwan 82 , Nantong 83 , Beijing 84 and Wuhan 85 , many and various anthropogenic sources, including industrial processes, solvent utilization, vehicle exhaust and gasoline evaporation, were commonly apportioned as the main contributors of VOCs. In these cities, biogenic sources only made a minor contribution.…”
Section: Vocsmentioning
confidence: 99%